Real‐time tracking of the self‐assembled growth of a 3D Ge quantum dot lattice in an alumina matrix. Issue 4 (24th July 2020) - Shaji, Ashin; Micetic, Maja; Halahovets, Yuriy; Nadazdy, Peter; Matko, Igor; Jergel, Matej; Majkova, Eva; Siffalovic, Peter
Abstract : Real‐time X‐ray scattering reveals the growth of 3D correlated quantum dots in situ during ion beam deposition. Abstract : A laboratory in situ grazing‐incidence small‐angle X‐ray scattering (GISAXS) tracking of the self‐assembled growth of a regular 3D Ge quantum dot (QD) structure in an amorphous Al2 O3 matrix during the ion beam sputter deposition of a periodic Ge/Al2 O3 multilayer on silicon is reported. A 573 K substrate temperature proved to be necessary to achieve the self‐assembly effect. Relying on a fast repeated acquisition of GISAXS patterns, the temporal evolution of the growing 3D Ge QD structure was analyzed bilayer by bilayer to determine its type, lateral and vertical correlation lengths, and inter‐QD distance. The QD structure was found to have body‐centered tetragonal lattice type with ABA stacking, with the lattice parameters refined by fitting the final GISAXS pattern relying on a paracrystal model. A single set of paracrystal parameters enables one to simulate the temporal evolution of the in situ GISAXS patterns throughout the deposition process, suggesting that the Ge QD self‐assembly is driven from the very beginning solely by the growing surface morphology. Ex situ GISAXS and X‐ray reflectivity measurements along with a cross‐section high‐resolution transmission electron microscopy analysis complete the study.